Phytochemical profiling and antioxidant evaluation of root ethanol extract of Maesa indica (Roxb.) sweet - Pooja K P; Shrishail H C (Creative Pharma Assent, 2025)
Background: Healing herbs have long been used in traditional medicine due to their therapeutic properties and rich content of bioactive molecules. Despite its traditional applications, research on the root part of Maesa indica is scarce. This study focuses on exploring the phytochemical composition and antioxidant potential of the ethanol extract of M. indica roots. Methodology: Secondary metabolites were identified using Liquid Chromatography–Quadrupole Time-of-Flight Mass Spectrometry (LC-Q-TOF-MS). Antioxidant activities were evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay and the metal chelating activity assay. Quantification of total phenolic content (TPC) and flavonoids was also conducted. Results and Discussion: Preliminary phytochemical analysis revealed the presence of flavonoids, phenols, steroids, and saponins. LC-Q-TOF-MS profiling identified seven primary secondary metabolites. The root extract exhibited high phenolic content (380.91 ± 23.52 µg/mg) and moderate flavonoid concentration (114.21 ± 6.25 µg/mg). Antioxidant activity of root extract was demonstrated by DPPH radical scavenging showed strong activity (IC₅₀: 88.78 µg/mL) and moderate ferrous ion chelating activity (IC₅₀: 172.31 µg/mL), suggesting effective free radical neutralization. Conclusion: The findings highlight the root extract of M. indica as a promising source of natural antioxidants. Compared to previous studies on aerial parts of the plant, the root extract offers comparable or enhanced antioxidant capacity, suggesting its value in future pharmaceutical and nutraceutical formulations